Self-generated thoughts and depression: from daydreaming to depressive symptoms - Marchetti, Igor; Van de Putte, Eowyn; Koster, Ernst H. (Frontiers in Human Neuroscience, 2014)
Human minds often engage in thoughts and feelings that are self-generated rather than stimulus-dependent, such as daydreaming. Recent research suggests that under certain circumstances, daydreaming is associated with adverse effects on cognition and affect. Based on recent literature about the influence of resting mind in relation to rumination and depression, this questionnaire study investigated mechanisms linking daydreaming to depressive symptoms. Specifically, an indirect effect model was tested in which daydreaming influences depressive symptoms through enhancing self-focus and ruminative thought. Results were in line with the hypothesis and several alternative pathways were ruled out. The results provide initial supportive evidence that daydreaming can influence depressive symptoms through influences on self-focus and rumination. Further research should use prospective or experimental designs to further validate and strengthen these conclusions.